Pemodelan Premi Asuransi Jiwa Dwiguna Unit Link dengan Metode Annual Ratchet dan Hukum Gompertz - Aldila Nur Indah Berliana Ratam; Marisa; Agus Irawan; Nasrullah (Mandalika Mathematics and Educations Journal, 2026)
The risk of death is one of the risks that can have a significant impact on an individual’s financial condition. Therefore, protection through life insurance is required. Unit-linked endowment life insurance combines protection and investment benefits, with the premium amount affecting both. This study is a quantitative research with an actuarial modeling approach that aims to model the premium of unit-linked endowment life insurance based on stock investment using the annual ratchet method and Gompertz’s law. Stock returns and volatility are used as the basis for determining investment benefits under the annual ratchet method, using stock data for PT Bank Central Asia Tbk. The annual ratchet method is applied to protect the investment value from market declines by implementing cap and floor limits. Survival and mortality probabilities are modeled using Gompertz’s law. The results of the study show that, based on mortality modeling using Gompertz’s law and the annual ratchet mechanism, the net single premium for unit-linked endowment life insurance that must be paid at the beginning of the contract was Rp 129,098,509. These results show that applying the annual ratchet method can protect against fluctuations in investment value while accounting for mortality risk in premium determination, making the resulting model an alternative for developing more stable unit-linked life insurance products.